Heuristic Workaround Behavior and Operational Resilience Under Rigid ERP Constraints: A Mixed-Methods Study in the Pharmaceutical Industry - Shonifah Dzikro Auji; Anita Safitri; Achmad Fitro; Muhammad Fajar Wahyudi Rahman (Edutech Publishing Media, 2026)
The pharmaceutical industry is governed by one of the most rigorous regulatory frameworks in the world, requiring strict adherence to Standard Operating Procedures (SOPs) and Good Manufacturing Practice (GMP) while also dealing with the constraints of rigid and unstable Enterprise Resource Planning (ERP) systems. This study seeks to identify the cognitive problem-solving mechanisms and heuristic workaround practices used by employees in responding to ERP-related constraints, examine their mediating role in the development of operational resilience, and explore the contextual factors that support or restrict such adaptive behaviors. The study employed a mixed methods approach with an exploratory sequential design. The qualitative phase involved participatory observation and in-depth interviews with 4 key informants, followed by a quantitative phase utilizing a census sampling technique and PLS-SEM analysis among 101 operational employees at a pharmaceutical company in Sidoarjo, East Java. The findings identified four pragmatic and rational forms of workaround behavior: ERP data adaptation, manual hardfile backup, cash-based incentive payments for interns outside the payroll system, and transaction input prior to formal purchase order processing. The structural test results showed that employee heuristic workaround behavior fully mediates the relationship between rigid ERP constraints and operational resilience, with a path coefficient of 0.443 and a significance value of p < 0.001. These findings indicate that operational resilience is not determined solely by formal organizational systems, but also develops through the collective cognitive adaptive capacity of employees, which should be recognized and managed strategically by organizations.